Political culture in Libya and its impact on political participation (Comprehensive Journal of Science, 2026)
This research highlights the impact of Libya's inherited political culture, historically shaped by a blend of tribalism, authoritarian legacy, and the marginalization of political parties. This has resulted in weak or limited political participation, often subservient. Traditional values ​​and sub-national loyalties dominate at the expense of civic awareness. Even after 2011, no attempts at democratic participation have been observed. The ruling elites continue to maintain power by undermining genuine political participation and exploiting the illusion of "formal democracy" while denying the people the substance of power. This obstructs reform and allows those who benefit from the status quo to remain an obstacle to change
Keywords: awareness, traditional political values (tribe and regionalism), political participation, political legitimacy, democratic transition, roles of elites, political socialization